PWE-085 Analysis of the clonality of Barrett's oesophagus glands reveals they are clonal and establishes a common stem cell for glandular and squamous epithelium. (23rd September 2015) - Nicholson, A M; Graham, T A; Simpson, A I; Humphries, A; Wright, N A; McDonald, S A C; Jankowski, J A
Abstract : Introduction: Barrett's oesophagus (BE) describes the change from the normal keratinised squamous epithelium of the oesophagus into an intestinal columner phenotype. BE is the only known precursor of oesophageal adenocarcinoma. Little is known about the origin and stem cell architecture of BE glands, or about the mechanism of gland spread. Here we have used non-pathologic mitochondrial DNA (mtDNA) mutations as a marker of clonal expansion to investigate the origin and spread of clones within BE. Methods: Enzyme histochemistry for cytochrome-c oxidase (CCO) and succinate dehydrogenase (SDH) was performed on frozen sections of BE. Laser-capture microdissected cells were taken from glandular and squamous epithelium. Mutations were indentified using a nested PCR protocol and sequencing of the entire mtDNA. Results: CCO deficient glands, were seen in sections of a gastric type BE (n=2/2), but not within intestinal metaplasia (n=3/3). Where CCO deficient glands were seen all cells contained the same mutation, suggesting a common stem cell origin. Mixed glands containing CCO positive and negative lineages were observed suggesting multiple stem cells may be present in the one gland. Patches of adjacent glands varying between 2-7 glands containing the same mutation were seen, indicating that BE glands spread by fission. In one case, cells from CCO deficient squamous tissue shared the same mtDNA mutation as cells from underlying CCO deficient glandular epithelium, suggesting the two tissue compartments are derived from a common progenitor cell Conclusion: mtDNA mutation burden differs between histological subtype of BE, perhaps reflecting in part the differing epigenetic stimuli from the environment such as acid and bile, as well as the histological organisation and topography of the stem cell gland unit. Patches of adjacent glands can share the same mtDNA mutation, indicating that glands spread by fission. Finally we have shown the both glandular and squamous tissue can be derived from a common progenitor cell. Taken together these findings indicate that distinct oesophageal lineages may be topographically and developmentally interconnected making eradication of some oesophageal squamous lineages necessary in the prevention of EA.